The National Hockey League, 1917-1967 : a year-by-year statistical history - Wright, Marshall D. (McFarland & Co., 2010)
"This is a statistical history of the National Hockey League in its first fifty seasons. It provides every statistic for every player for every game, including playoff games. A full introduction puts the tremendous amount of data contained within the book in its historical context, and each chapter then recounts a single season"--Provided by publisher